trouver le resultat de :

(+14)-(-6)= .... diviser par 3

(-25)-(-16)=.....diviser par 3

(-6)-(+9)= .....diviser par 3

(+3.2)-(-4.7)=....diviser par3

1
(14)-(-6) = 20 donc. (14)-(-6) = 60 diviser par 3. ; (-25)-(-16) = -9, donc (-25)-(-16) =-9. ; (-6)-(9) = 15 donc (-6)-(9) = 45 divise par 3 ; (3,2)-(-4,7) = 7,9 donc (3,2)-(-4,7) = 23,7 divisé par 3.

Réponses

2013-10-18T18:21:57+02:00
(+14)-(-6)=14+6=20  donc 60 divisé par 3
(-25)-(-16)=-25+16=-9 donc -27 divisé par 3
(-6)-(+9)=-6-9=-15  donc -45 divisé par 3
(+3,2)-(-4,7)=3,2+4,7=7,9  donc 23,7 divisé par 3